High oxygen barrier, clay and chitosan-based multilayer thin films: an environmentally friendly foil replacement. Issue 1 (1st March 2013) - Kirkland, Christopher; Priolo, Morgan A.; Laufer, Galina; Grunlan, Jaime C.
Abstract : Multilayered thin films, with high oxygen barrier, were deposited from water using chitosan (CH), polyacrylic acid (PAA), and montmorillonite (MMT) clay. Layer-by-layer assembly of ten "quadlayers" of CH/PAA/CH/MMT (<100 nm thick) on polylactic acid (PLA) and polyethylene terephthalate (PET) films, commonly used for food packaging, reduced the oxygen transmission rate (OTR) of PLA and PET films by two orders of magnitude under dry conditions. At 38°C and 90% RH, the OTR of 500 μm PLA was reduced from 50 to 4·6 cc/(m2 day atm), which is lower than 179 μm PET film under the same conditions. This high gas barrier is believed to be due a to a nanobrick wall structure present in this thin film, where clay platelets act as bricks held together by polymeric mortar. These assembled thin films are also very transparent, which combined with ambient processing and the use of renewable and food contact approved ingredients, makes this a promising foil replacement technology. Multilayered thin films, with high oxygen barrier, were deposited from water using chitosan (CH), polyacrylic acid (PAA), and montmorillonite (MMT) clay. Layer-by-layer assembly of ten "quadlayers" of CH/PAA/CH/MMT (<100 nm thick) on polylactic acid (PLA) and polyethylene terephthalate (PET) films, commonly used for food packaging, reduced the oxygen transmission rate (OTR) of PLA and PET films by two orders of magnitude under dry conditions. At 38°C and 90% RH, the OTR of 500 µm PLA was reduced from 50 to 4·6 cc/(m2 day atm), which is lower than 179 µm PET film under the same conditions. This high gas barrier is believed to be due a to a nanobrick wall structure present in this thin film, where clay platelets act as bricks held together by polymeric mortar. These assembled thin films are also very transparent, which combined with ambient processing and the use of renewable and food contact approved ingredients, makes this a promising foil replacement technology.